Child physical activity levels and associations with modifiable characteristics in centre‐based childcare. (25th February 2015) - Bell, A. Colin; Finch, Meghan; Wolfenden, Luke; Fitzgerald, Michael; Morgan, Philip J.; Jones, Jannah; Freund, Megan; Wiggers, John
Abstract Objective: To describe children's physical activity levels during childcare and associations with modifiable characteristics. Methods: A cross‐sectional study of 328 preschool children (43% girls; age 3–5 years) and 145 staff from 20 long day care centres in the Hunter Region of NSW, Australia. Pedometers assessed child physical activity levels. Centre characteristics and staff attitudes and behaviours towards children's physical activity were assessed using surveys, interviews and observational audit. Results were analysed using descriptive statistics and linear regression. Results: Over the measurement period, average step count of children was 15.8 (SD=6.8) steps/minute. Four‐year‐olds had the highest step counts (16.4, SD=7.1, p=0.03) with no differences by sex. Step counts were significantly higher in centres that had a written physical activity policy (+3.8 steps/minute, p=0.03) and where staff led structured physical activity (+3.7 steps/minute, p<0.001) and joined in active play (+2.9 steps/minute, p=0.06). Conclusions: Written physical activity policy, structured staff‐led physical activity and staff joining in active play were associated with higher levels of physical activity. Implications: Childcare physical activity interventions should consider including strategies to encourage written physical activity policies and support structured staff led physical activities.